Comparison of Face Types in Chinese Women Using Three-Dimensional Computed Tomography - Zhou, Rong-Rong; Zhao, Qi-Ming; Liu, Miao (Facial Plastic Surgery, 2015)
This study compared inverted triangle and square faces of 21 young Chinese Han women (18–25 years old) using three-dimensional computed tomography images retrieved from a records database. In this study, 11 patients had inverted triangle faces and 10 had square faces. The anatomic features were examined and compared. There were significant differences in lower face width, lower face height, masseter thickness, middle/lower face width ratio, and lower face width/height ratio between the two facial types (p < 0.01). Lower face width was positively correlated with masseter thickness and negatively correlated with gonial angle. Lower face height was positively correlated with gonial angle and negatively correlated with masseter thickness, and gonial angle was negatively correlated with masseter thickness. In young Chinese Han women, inverted triangle faces and square faces differ significantly in masseter thickness and lower face height.
Keywords: inverted triangle face type; square face type; masseter thickness; gonial angle; cosmetic surgery; morphometry; 3D-CT